Ekolojik Sistemler Teorisi Kavramları ile Bir Vaka Değerlendirilmesi - Akkaya, M.Fatih (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2021)
Bu çalışma, anne ve çocuk ile gerçekleştirilen 8 oturumluk bir vaka analizinden oluşmaktadır. Danışan K. 9 yaşındadır ve tek çocuktur. Terapiye geliş sebebi, anne ve babanın boşanmasından sonra değişen yaşam koşulları ve değişen yaşam ile ilgili uyum sorunlarıdır. Danışma hedefleri şu şekilde belirlenmiştir: Danışanın duygularını ifade etmesi, danışanın annesinden ayrışması, annenin kendi ailesinden ayrışması, sınırların netleştirilmesi ve danışan ve annesinin kendilerine ait yeni bir alt sistem kurabilmeleri. Danışan K. ve annesi ile ayrı ayrı seanslar haftalık gerçekleştirilmiştir. Her seans sonrası süpervizyon desteği alınmıştır. Bu çalışma kapsamında ele alınan vaka, ekolojik sistemler teorisi bağlamında analiz edilmiştir. Ekolojik sistemler teorisi, hem gelişim psikolojisinde, hem de kültür ve insan gelişiminin incelenmesinde ileri sürülen bir yaklaşımdır. Bunun yanında sistemik terapiler, danışanın ve danışanın sorunlarının farklı sistemlerin etkileşim yüzeylerinde algılanması gerektiğini savunur. Çalışma sonunda, bir sistemin üyesi olan danışanla ekolojik sistemler teorisi bağlamında çalışılabileceği görülmüştür.

This study consists of an 8-session case analysis with mother and child. Client K. is 9 years old and is an only child of family. The reason of coming to therapy is the changing living conditions and adjustment problems related to the changing life after the divorce of the parents. Counseling goals were determined as follows: The client's expression of feelings, the separation of the client from her mother, the separation of the mother from her own family, the clarification of boundaries, and the ability of the client and her mother to establish a new subsystem of their own. Separate sessions were held weekly with the client K. and her mother. Supervision support was received after each session. The case covered in this study has been analyzed in the context of ecological systems theory. Ecological systems theory is an approach put forward both in developmental psychology and in the study of culture and human development. In addition, systemic therapies argue that the client and the client's problems should be perceived on the interaction surfaces of different systems. At the end of the study, it was seen that the client, who is a member of a system, can be studied in the context of ecological systems theory.
A Case Evaluation With the Concepts of Ecological Systems Theory
Keywords: Ekolojik Sistemler Teorisi; Sistemik Terapi; Vaka Analizi; Boşanma; Danışan-terapist; Ecological Systems Theory; Systemic Therapy; Case Study; Divorce; Client-therapist